Serum spexin differed in newly diagnosed type 2 diabetes patients according to body mass index and increased with the improvement of metabolic status - Gu, Liping; Yan, Shuai; Huang, Yunhong; Yang, Jiaying; Peng, Yongde; Wang, Yufan (Frontiers in Endocrinology, 2022)
Objective The aim of this study was to explore serum spexin levels in newly diagnosed type 2 diabetes mellitus (T2DM) patients with different body mass indexes (BMIs) and to investigate the changes of spexin after improvement of metabolic indicators. Methods A total of 323 newly diagnosed T2DM patients from national Metabolic Management Center (MMC) in Shanghai General Hospital were recruited. T2DM patients were categorized into three groups: diabetes with obesity group (DM-OB group, BMI≥28 kg/m2, n=89), diabetes with overweight group (DM-OV group, 24≤BMI<28 kg/m2, n=161), and diabetes with normal weight group (DM-NW group, 18≤BMI<24 kg/m2, n=73). In addition, 41 volunteers with normal glucose tolerance (NGT) were used as controls. Spexin and metabolic parameters were compared at baseline, and changes after MMC follow-up in 100 DM patients were investigated. Results In the DM-OB group, the level of spexin was significantly lower than that in the DM-OV group and the DM-NW group (P < 0.01). Spexin was significantly negatively related to body mass index (BMI, β=-0.214, P<0.001), waist circumference (β=-0.249, P<0.001), visceral fat area (VFA, β=-0.214, P<0.001), and subcutaneous fat area (SFA, β=-0.265, P<0.001) after adjustment for age and sex. Among all the metabolic indicators, the decline in BMI in the DM-OB group was the most obvious among those in the three groups (-3.7 ± 0.8 kg/m2 vs. -0.9 ± 0.3 kg/m2 vs. 0.7 ± 0.6 kg/m2, P<0.01) after one year of MMC standardized management. The serum spexin level in the DM-OB group increased the most (1.00 ± 0.10 ng/mL vs. 0.49 ± 0.06 ng/mL in DM-OV group and 0.58 ± 0.09 ng/mL in DM-NW group, P < 0.001). Conclusions Serum spexin differed in newly diagnosed T2DM patients according to BMI and was lowest in the DM-OB group. With the improvement of metabolic indicators, especially the decline in BMI, serum spexin increased significantly after MMC management.